Treatment of Chronic Phantom Limb Pain Using a Trauma-Focused Psychological Approach - C de Roos; AC Veenstra; A de Jongh; ME den Hollander-Gijsman; NJA van der Wee; FG Zitman; YR van Rood (Pain Research and Management)
BACKGROUND: Chronic phantom limb pain (PLP) is a disabling chronic pain syndrome for which regular pain treatment is seldom effective. Pain memories resulting from long-lasting preamputation pain or pain flashbacks, which are part of a traumatic memory, are reported to be powerful elicitors of PLP.